Evaluating energy efficiency of lighting system in university library building - Ahmad Jasmi, Siti Zulaiha; Ayob, Mohd Fairullazi (2015)
Library buildings consume a large quantity of energy for user services and ensuring the comfort in the building which these have produced a considerable waste on the energy usage. Lighting system is one of the largest contributors in the energy consumption and operational cost of a library building. The implementation of energy efficiency of lighting system is needed in order to reduce the energy consumption of lighting system. Therefore, the purpose of this paper is to study energy efficiency of lighting system in the university library building. The library building at the International Islamic University Malaysia (IIUM) is chosen as the subject matter of the study. A semi-structured interview was carried out to interview four respondents who currently in-charge in the IIUM library building operation. The results revealed the majority of the respondents agreed that the IIUM Library building did not implement the energy efficient criteria in fixing the lighting system which lead to high energy consumption. A proper guideline to improve the energy efficiency of lighting system in IIUM library was identified as the top priority strategy which proposed by the majority of the respondents in the study.